Biaxially oriented polypropylene film and laminate
A biaxially oriented polypropylene film with a specific resin blend in the base layer addresses the issue of using recycled materials by maintaining rigidity and heat resistance, enhancing film formability and reducing environmental impact.
Patent Information
- Application Number
- JP2024170060
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-12-12
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-19
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Biaxially oriented polypropylene films face challenges in maintaining rigidity and heat resistance when using recycled raw materials due to the presence of foreign materials, which deteriorate film performance.
A biaxially oriented polypropylene film with a base layer containing recycled materials blended with a specific resin mixture, including polypropylene resin, recycled raw materials, and optionally a propylene/α-olefin random copolymer, ensuring a high elastic modulus, controlled dimensional stability, and heat resistance by setting conditions such as melt flow rate, melting peak temperature, and enthalpy of fusion.
The film maintains excellent film formability, rigidity, and heat resistance without being affected by foreign materials, promoting the use of recycled materials and reducing environmental impact.
Smart Images

Figure 2024177238000001 
Figure 2024177238000002 
Figure 2024177238000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a biaxially oriented polypropylene film and a laminate using the film. [Background technology]
[0002] Conventionally, oriented polypropylene films have been widely used for various applications including packaging materials, taking advantage of their excellent transparency, mechanical strength, moisture resistance, rigidity, etc. In recent years, from the viewpoint of reducing the environmental load, efforts have been made to reduce the amount of polypropylene used, such as by reducing the thickness.
[0003] For thin stretched polypropylene films, users demand that the film maintain its rigidity so as not to impair the feeling of use, and therefore the film must have a significantly improved rigidity compared to conventional stretched polypropylene films. In addition, since the film is printed or laminated, the film must have sufficient heat resistance and dimensional stability while still having improved rigidity. Thus, biaxially stretched polypropylene films are known that have been given high heat resistance, rigidity, etc. by adjusting the thermal shrinkage rate in the machine direction (MD) and the transverse direction (TD) of the film and the impact strength (impact resistance) (see, for example, Patent Document 1).
[0004] In addition, with the promotion of the Sustainable Development Goals (SDGs), efforts to realize an environmentally friendly recycling-based society include, for example, the use of renewable energy to suppress the emission of greenhouse gases such as carbon dioxide, which is considered to be one of the causes of global warming. In the field of resin films, films that use plant-derived raw materials (biomass raw materials) instead of petroleum-derived raw materials have been proposed (see, for example, Patent Document 2). Plant-derived raw materials are carbon-neutral resources, and are therefore effective as resources that can contribute to reducing environmental loads compared to petroleum-derived raw materials.
[0005] Another environmentally friendly initiative is the use of recycled materials. Recycled materials that are expected to be used as materials to make up films include recycled films, as well as post-industrial recycled materials that reuse materials generated during the manufacturing process before products are released to the market, such as scraps and surplus products generated during film production, and post-consumer recycled materials that collect used products in the market and turn them into recycled resources. In addition, mechanical recycling, a method of crushing, melting, and forming into pellets when reusing, is commonly used to mold these recycled materials.
[0006] Among these mechanically recycled materials, those used for oriented polypropylene mainly use polypropylene as the main raw material. Polypropylene may contain various kinds of resins, additives such as antistatic agents and antiblocking agents, as well as resins used in masterbatches of these additives, and other materials different from the main raw material resin in an unspecified ratio. These different materials contained in the recycled materials are technically and economically difficult to remove. Therefore, the recycled materials are reused with the different materials remaining.
[0007] In biaxially oriented polypropylene films with high rigidity and high heat resistance that use such recycled materials, the film's rigidity (elastic modulus, etc.) and film performance (heat resistance, etc.) tend to decrease due to the influence of different materials contained in the recycled materials. Therefore, in the past, it was not suitable to use this type of recycled material in the production of biaxially oriented polypropylene films with high rigidity and high heat resistance, and it was not put to practical use.
[0008] However, due to social demands for environmental consideration, there is a demand to use recycled raw materials in order to contribute to reducing greenhouse gas emissions and efficiently using petroleum resources. In addition, the use of recycled raw materials is economically rational and is becoming more useful. Therefore, the inventors conducted extensive research and came to invent a film that has excellent film formability without compromising the film performance even when using recycled raw materials containing different materials. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2014-055283 A [Patent Document 2] JP 2021-133509 A Summary of the Invention [Problem to be solved by the invention]
[0010] The present invention has been made in consideration of the above-mentioned points, and provides a biaxially oriented polypropylene film and laminate that have excellent film formability without impairing rigidity and heat resistance even when made from recycled raw materials. [Means for solving the problem]
[0011] That is, the first invention relates to a biaxially stretched polypropylene film, which comprises a base material layer, and a surface layer laminated on one or both sides of the base material layer, and a recycled raw material derived from a molded article mainly composed of a polypropylene resin is blended in the base material layer. Among them, the elastic modulus in the longitudinal (MD) direction measured in accordance with JIS K 7127 (1999) is 2.0 GPa or more, and the elastic modulus in the transverse (TD) direction is 4.0 GPa or more. When the temperature is raised from 30 °C to 150 °C at a rate of 20 °C / min with a thermomechanical analyzer (TMA) and a load of 0.32 N is applied in the longitudinal (MD) direction, the difference (L140 - L120) between the dimensional change rate L140 (%) in the longitudinal (MD) direction at 140 °C and the dimensional change rate L120 (%) in the longitudinal (MD) direction at 120 °C is 15 or less. The base material layer is composed of a resin mixture in which at least two different resins are mixed, including 55% by weight or more of a polypropylene resin (A) with a mesopentad fraction (mmmm) of 95% or more, and 5 - 25% by weight of the recycled raw material (B) with a melt flow rate (MFR) of 3.0 - 11.0 g / 10 min, a melting peak temperature measured in accordance with JIS K 7122 (2012) with a differential scanning calorimeter (DSC) of 145 - 170 °C, and a melting enthalpy (ΔH) of 87.0 J / g or more.
[0012] The second invention relates to a biaxially stretched polypropylene film according to the first invention, wherein the recycled raw material (B) has a crystallization temperature of 105 °C or more measured in accordance with JIS K 7122 (2012) with a differential scanning calorimeter (DSC).
[0013] The third invention relates to a biaxially stretched polypropylene film according to the first or second invention, wherein the recycled raw material (B) satisfies the relationship of molecular weight distribution (Mw / Mn, Mz+1 / Mw) obtained by gel permeation chromatography (GPC) measurement: Mw / Mn < Mz+1 / Mw and Mz+1 / Mw ≥ 4.7.
[0014] A fourth invention relates to the biaxially oriented polypropylene film according to the first or second invention, wherein the base layer contains 10% by weight or less of a propylene-α-olefin random copolymer (C).
[0015] A fifth aspect of the present invention relates to the biaxially oriented polypropylene film according to the third aspect of the present invention, wherein the base layer contains 10% by weight or less of a propylene-α-olefin random copolymer (C).
[0016] A sixth aspect of the present invention relates to a laminate in which a sealant film is laminated onto the biaxially oriented polypropylene film according to the first or second aspect of the present invention.
[0017] A seventh aspect of the present invention relates to a laminate in which a sealant film is laminated on the biaxially oriented polypropylene film according to the third aspect of the present invention.
[0018] An eighth aspect of the present invention relates to a laminate in which a sealant film is laminated to the biaxially oriented polypropylene film according to the fourth aspect of the present invention.
[0019] A ninth aspect of the present invention relates to a laminate in which a sealant film is laminated to the biaxially oriented polypropylene film according to the fifth aspect of the present invention.
[0020] A tenth invention relates to the laminate according to the sixth invention, wherein the sealant film is a non-oriented polypropylene film.
[0021] An eleventh invention relates to the laminate according to the seventh invention, wherein the sealant film is a non-oriented polypropylene film.
[0022] A twelfth invention relates to the laminate according to the eighth invention, wherein the sealant film is a non-stretched polypropylene film.
[0023] A thirteenth aspect of the present invention relates to the laminate according to the ninth aspect of the present invention, wherein the sealant film is a non-oriented polypropylene film. Effect of the Invention
[0024] According to the first aspect of the present invention, the biaxially oriented polypropylene film is a laminated film comprising a base layer and a surface layer laminated on one or both sides of the base layer, the base layer containing recycled raw materials derived from a molded product mainly made of polypropylene resin, the laminated film being in compliance with JIS K The laminated film has a modulus of elasticity in the machine direction (MD) of 2.0 GPa or more and a modulus of elasticity in the transverse direction (TD) of 4.0 GPa or more, as measured in accordance with JIS K 7127 (1999), and a difference (L140-L120) between the dimensional change rate L140 (%) in the machine direction (MD) at 140°C and the dimensional change rate L120 (%) in the machine direction (MD) at 120°C when the temperature is increased from 30°C to 150°C at a rate of 20°C / min and a load of 0.32 N is applied in the machine direction (MD) is 15 or less, the base layer comprises 55% by weight or more of polypropylene resin (A) having a mesopentad fraction (mmmm) of 95% or more, a melt flow rate (MFR) of 3.0 to 11.0 g / 10 min, and a thermal expansion coefficient (SSC) of 1.0 to 1.0 g / 10 min is measured in accordance with JIS K 7127 (1999). 7122(2012) is 145 to 170 ° C. and the melting enthalpy (ΔH) is 87.0 J / g or more, and 5 to 25 wt % of the recycled raw material (B) is a resin mixture containing at least two different resins. Therefore, it is possible to obtain excellent film formability without impairing the film properties such as rigidity and heat resistance, regardless of the presence or absence of different materials in the recycled raw material.
[0025] According to the biaxially oriented polypropylene film of the second invention, in the first invention, the recycled raw material (B) has a crystallization temperature of 105°C or higher as measured by a differential scanning calorimeter (DSC) in accordance with JIS K 7122 (2012), so that the crystallization rate is fast and good rigidity can be obtained.
[0026] According to the biaxially stretched polypropylene film according to the third invention, in the first or second invention, since the recycling raw material (B) satisfies the relationship of molecular weight distribution (Mw / Mn, Mz+1 / Mw) obtained by gel permeation chromatography (GPC) measurement of Mw / Mn < Mz+1 / Mw and Mz+1 / Mw ≧ 4.7, high rigidity can be maintained.
[0027] According to the biaxially stretched polypropylene film according to the fourth invention, in the first or second invention, since the propylene-α-olefin random copolymer (C) is contained in the base material layer at 10% by weight or less, the stretchable temperature range of the film can be widened, the defective rate due to stretching marks can be reduced, and high production efficiency can be achieved.
[0028] According to the biaxially stretched polypropylene film according to the fifth invention, in the third invention, since the propylene-α-olefin random copolymer (C) is contained in the base material layer at 10% by weight or less, the stretchable temperature range of the film can be widened, the defective rate due to stretching marks can be reduced, and high production efficiency can be achieved.
[0029] According to the laminate according to the sixth invention, since the sealant film is laminated on the biaxially stretched polypropylene film described in the first or second invention, even if the recycling raw material is blended, the film properties such as rigidity and heat resistance are not impaired, and it can be suitably used as a film product such as a packaging film for reducing environmental load.
[0030] According to the laminate according to the seventh invention, since the sealant film is laminated on the biaxially stretched polypropylene film described in the third invention, even if the recycling raw material is blended, the film properties such as rigidity and heat resistance are not impaired, and it can be suitably used as a film product such as a packaging film for reducing environmental load.
[0031] According to the laminate of the eighth invention, a sealant film is laminated to the biaxially oriented polypropylene film described in the fourth invention. Therefore, even if recycled raw materials are mixed in, the film properties such as rigidity and heat resistance are not impaired, and the laminate can be suitably used as a film product such as a packaging film that aims to reduce the environmental load.
[0032] According to the laminate of the ninth invention, a sealant film is laminated to the biaxially oriented polypropylene film described in the fifth invention. Therefore, even when recycled raw materials are mixed in, the film properties such as rigidity and heat resistance are not impaired, and the laminate can be suitably used as a film product such as a packaging film that aims to reduce the environmental load.
[0033] According to the laminate of the tenth aspect of the present invention, since the sealant film is a non-oriented polypropylene film in the sixth aspect of the present invention, excellent recyclability and heat seal strength can be obtained.
[0034] According to the laminate of the eleventh invention, in the seventh invention, since the sealant film is a non-oriented polypropylene film, excellent recyclability and heat seal strength can be obtained.
[0035] According to the laminate of the twelfth invention, in the eighth invention, since the sealant film is a non-oriented polypropylene film, excellent recyclability and heat seal strength can be obtained.
[0036] According to the laminate of the thirteenth invention, in the ninth invention, since the sealant film is a non-oriented polypropylene film, excellent recyclability and heat seal strength can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0037] The biaxially oriented polypropylene film according to one embodiment of the present invention is a laminated film having a base layer and a surface layer laminated on one or both sides of the base layer. In this biaxially oriented polypropylene film, recycled materials are blended into the base layer. The biaxially oriented polypropylene film of the present invention is produced by a known film production method such as a T-die method. This film is suitably used as a packaging film for, for example, food, daily necessities, miscellaneous goods, cosmetics, medicines, and other products. The packaging film can also be appropriately made into a packaging bag.
[0038] The physical properties required for this biaxially oriented polypropylene film in various applications such as packaging films are a modulus of elasticity in the machine direction (MD) of 2.0 GPa or more and a modulus of elasticity in the transverse direction (TD) of 4.0 GPa or more. The dimensional change rate in the machine direction (MD) at 140°C when the temperature was increased from 30°C to 150°C at a rate of 20°C / min and a load of 0.32 N was applied in the machine direction (MD) was 1.0 GPa or more. 140 )% and the dimensional change rate in the machine direction (MD) at 120℃ (L 120 )% difference (L 140 -L 120 ) is 15 or less, and the heat shrinkage rates in the machine direction (MD) and the transverse direction (TD) are each 10% or less.
[0039] The elastic modulus is a value measured by a test method for tensile properties conforming to JIS K 7127 (1999). The elastic modulus is used as one of the indicators of the rigidity of a film. A film with a higher elastic modulus value has higher rigidity and stronger stiffness. By having a modulus of elasticity in the machine direction (MD) of 2.0 GPa or more and a modulus of elasticity in the transverse direction (TD) of 4.0 GPa or more, the biaxially oriented polypropylene film has excellent processability suitable for various applications such as packaging films. If the modulus of elasticity in the machine direction (MD) or the transverse direction (TD) is too low, the film may have poor processability and may deform easily, resulting in reduced productivity.
[0040] The dimensional change rate indicates the rate at which a film is deformed by temperature rise, and is used as an index of dimensional stability such as the film's elongation performance, etc. In particular, it is dimensional stability assuming a state in which the film expands and contracts due to tension being applied to the film during secondary processing such as deposition, printing, and lamination of metal or inorganic oxide layers.
[0041] In the biaxially stretched polypropylene film of the present invention, the film was heated from 30°C to 150°C at a rate of 20°C / min using a thermomechanical analyzer (TMA), and a load of 0.32N was applied in the machine direction (MD). The dimensional change rate in the machine direction (MD) at 140°C was L 140 (%), dimensional change rate in the machine direction (MD) at 120℃ 120 (%), dimensional change rate L 140 and dimensional change rate L 120 Difference with (L 140 -L 120 ) is required to be 15 or less. A difference in dimensional change rate (dimensional stability) of 15 or less indicates that the rate of deformation due to temperature rise is small and the dimensional stability is excellent. If the difference in dimensional change rate is too large, the film is likely to deform due to temperature rise and the dimensional stability is poor. This may lead to reduced productivity, such as the occurrence of wrinkles during secondary processing such as printing, or a deterioration in appearance.
[0042] The heat shrinkage rate indicates the rate at which a film shrinks at a given temperature, and is used as an index of dimensional stability such as the shrinkage performance of the film. The biaxially oriented polypropylene film of the present invention is required to have a heat shrinkage rate of 10% or less in both the machine direction (MD) and the transverse direction (TD) when heated at 150°C for 5 minutes. A heat shrinkage rate of 10% or less indicates that the film is less likely to shrink at high temperatures and has excellent dimensional stability. If the heat shrinkage rate in either or both of the machine direction (MD) and the transverse direction (TD) is too large, the film is more likely to shrink at high temperatures and has poor dimensional stability. This may result in reduced productivity, such as wrinkles during the packaging process and poor appearance.
[0043] In addition, the biaxially stretched polypropylene film of the present invention preferably has the transparency required for applications such as packaging films. The transparency of the film is represented by the haze value measured in accordance with JIS K 7136 (2000). The preferred haze value for the film is 5.0% or less. If the haze value is too large, the transparency generally required for packaging films and the like is insufficient, which is undesirable.
[0044] The base layer is made of a resin mixture of at least two different resins containing 55% by weight or more of polypropylene resin (A) and 5 to 25% by weight of recycled material (B). In addition to the polypropylene resin (A) and recycled material (B), additives such as propylene-α-olefin random copolymer (C) and master batches containing antistatic agents and antiblocking agents are mixed into the base layer as necessary.
[0045] The polypropylene resin (A) must have a mesopentad fraction (mmmm) of 95% or more. The mesopentad fraction (mmmm) is an index of stereoregularity obtained by high-temperature nuclear magnetic resonance (NMR) measurement. The mesopentad fraction (mmmm) is measured using an FT-NMR device (manufactured by JEOL RESONANCE Co., Ltd., "JNM-ECA400"), 13 C-NMR measurement was performed. 0.6 mL of a mixture of deuterated orthodichlorobenzene: deuterated benzene = 8:2 (volume ratio) was added to 120 mg of sample, and the mixture was dissolved by heating to 135 ° C., and measurement was performed at 135 ° C. The mesopentad fraction was calculated by the method described in "Zambelli et al., Macromolecules, Vol. 6, p. 925 (1973)", and the peak assignment was based on the corrected version of the above literature described in "Macromolecules, Vol. 8, p. 687 (1975)". Observation kernel: 13 C(100MHz) Measurement mode: Single pulse proton broadband decoupling Pulse interval: 5 seconds Pulse width: 45° Shift reference: Solvent-derived signal = 132.39 ppm Accumulation count: 11,000 times
[0046] The pentad fraction, which indicates the degree of stereoregularity, is 13 This shows the proportion of isotactic sequences in pentad units in polypropylene molecular chains measured using C-NMR. This pentad fraction is the fraction (mmmm) of propylene monomers at the center of a chain in which five consecutive propylene units are meso-bonded. Specifically, 13 The intensity fraction of the mmmm peak among all absorption peaks in the methyl carbon region of the C-NMR spectrum is defined as an isotactic pentad unit.
[0047] By blending the base layer mainly with polypropylene resin having a mesopentad fraction (mmmm) of 95% or more, the crystallinity is improved, and the resin layer has excellent rigidity and heat resistance. If the blending ratio of this polypropylene resin is too low, the rigidity, heat resistance, etc. of the film may decrease. Similarly, if the mesopentad fraction of the polypropylene film is less than 95%, the rigidity, heat resistance, etc. of the film may decrease.
[0048] The recycled raw material (B) is a resin material derived mainly from polypropylene resin molded products, such as scraps and surplus products such as offcuts generated during film production, and other resin products, and is obtained by subjecting these to re-pelletization and other recycling processing. This recycled raw material includes resin molded products in which foreign materials that are difficult to remove and different from the main raw material, such as resins used in masterbatches of these additives, as well as resins different from the main raw material, remain. When recycled raw materials containing foreign materials remaining in such resin molded products are used as a constituent material of a biaxially oriented polypropylene film, this usually causes a decrease in the film's rigidity such as elastic modulus and heat resistance. In addition, in the biaxially oriented polypropylene film of the present invention, since the main raw material of the base layer is a highly crystalline polypropylene resin, the film performance may also be decreased if the recycled raw material contains a resin with low crystallinity.
[0049] Therefore, in the biaxially oriented polypropylene film of the present invention, by focusing on the melt flow rate, peak melting temperature, and enthalpy of melting of the recycled raw materials to be blended, and by using recycled raw materials having melt flow rate, peak melting temperature, and enthalpy of melting within specified conditions, it has been found that it is possible to obtain excellent film formability without impairing film properties such as rigidity and heat resistance, regardless of the presence or absence of foreign materials that cause a decrease in film properties.
[0050] That is, the recycled raw materials must have a melt flow rate (MFR) of 3.0 to 11.0 g / 10 min, a peak melting temperature of 145 to 170° C., and a melting enthalpy (ΔH) of 87.0 J / g or more. The preferable conditions of the melt flow rate (MFR), peak melting temperature, and melting enthalpy (ΔH) of the recycled raw materials are set taking into consideration the inclusion of different materials.
[0051] Melt flow rate (MFR) is used as an index of the fluidity of a resin. The higher the MFR value, the better the fluidity. Using recycled raw materials with too low an MFR may result in poor film formability due to insufficient fluidity. If the MFR is too high, it may result in poor film formability due to excessive fluidity. By using recycled raw materials with an MFR of 3.0 to 11.0 g / 10 min, good film formability can be obtained even if the recycled raw materials contain different materials.
[0052] The melting peak temperature is a value measured by a differential scanning calorimeter (DSC) in accordance with JIS K 7122 (2012). The melting peak temperature is used as one of the indicators of the heat resistance of a resin. If a recycled raw material with a melting peak temperature that is too low is used, the heat resistance will be insufficient, the thermal shrinkage rate of the film will increase, the film will be easily thermally deformed, and the rigidity and dimensional stability of the film may also decrease. In addition, since there are almost no cases in which the melting peak temperature of a resin molded product that can be used as a recycled raw material exceeds 170°C, it is considered that 170°C is an appropriate practical upper limit for the melting peak temperature. Therefore, by using a recycled raw material with a melting peak temperature of 145 to 170°C, good heat resistance can be obtained even if the recycled raw material contains a different material, and the thermal deformation of the film can be suppressed, and the deterioration of the rigidity and dimensional stability of the film can be suppressed.
[0053] The enthalpy of fusion (ΔH) is the energy required to melt a resin, measured with a differential scanning calorimeter (DSC) in accordance with JIS K 7122 (2012). The enthalpy of fusion is used as one of the indicators of the heat resistance of a resin. If recycled raw materials with too low an enthalpy of fusion are used, the heat resistance will be insufficient and the film will be prone to thermal deformation, and the rigidity and dimensional stability of the film may also decrease. The enthalpy of fusion of recycled raw materials must be 87.0 J / g or more from the viewpoint of thermal stability, which ensures good heat resistance even when the recycled raw materials contain different materials, suppressing thermal deformation of the film and preventing deterioration of the rigidity and dimensional stability of the film.
[0054] In addition, as the recycled raw material, the crystallization temperature is preferably 105°C or higher. The crystallization temperature is a value measured by a differential scanning calorimeter (DSC) in accordance with JIS K 7122 (2012). The crystallization temperature affects the rigidity, heat resistance, moldability, etc. of the biaxially stretched polypropylene film. If the crystallization temperature of the recycled raw material is too low, the heat resistance will decrease and the film will be prone to thermal deformation, which may reduce the rigidity and dimensional stability of the film. If the crystallization temperature of the recycled raw material is 105°C or higher, the crystallization rate will increase and good rigidity can be obtained, and the deterioration of the dimensional stability of the film can be suppressed.
[0055] Furthermore, for the recycled raw material, it is preferable that the relationship of the molecular weight distribution (Mw / Mn, Mz+1 / Mw) determined by gel permeation chromatography (GPC) measurement satisfies Mw / Mn < Mz+1 / Mw and Mz+1 / Mw ≥ 4.7. In the above molecular weight distribution, Mw is the weight average molecular weight, which is the value obtained by multiplying the molecular weight by the number of each molecule and then taking the average. Mn is the number average molecular weight, which is the value obtained by simply averaging the molecular composition by number.
[0056] Mz+1 (Z+1 average molecular weight) is more susceptible to the influence of the presence of higher molecular weights than Mw and is affected by the part with an even higher molecular weight than Mz. Note that Mz+1 is defined by the following formula (i), and Mz (Z average molecular weight) is defined by the following formula (ii). Mz+1 = Σ(Ni·Mi 4 ) / Σ(Ni·Mi 3 ) … (i) Mz = Σ(Ni·Mi 3 ) / Σ(Ni·Mi 2 ) … (ii)
[0057] Mw / Mn is an index representing the molecular weight distribution of each molecule. Also, Mz+1 / Mw is an index representing the molecular weight distribution of high molecular weight components. In the relationship of the molecular weight distribution, when Mw / Mn < Mz+1 / Mw, it means that the molecular weight distribution of the high molecular weight components is wide, there are very high molecular weight components, and the component ratio is further high. By using such a recycled raw material with many high molecular weight components, high rigidity can be maintained in the biaxially stretched polypropylene film. Also, Mz+1 / Mw at that time is 4.7 or more. If Mz+1 / Mw is too low, there is a risk that the component ratio of the high molecular weight components is insufficient and high rigidity cannot be maintained.
[0058] The propylene·α-olefin random copolymer (C) is a resin material that is blended as necessary in order to widen the temperature range in which the film can be stretched, reduce the defect rate due to stretching streaks, and achieve high production efficiency. By blending the propylene·α-olefin random copolymer in the base material layer of the film, it becomes easier to adjust the dimensional change rate in the MD direction in the TMA measurement, etc. The proportion when blending the propylene·α-olefin random copolymer is preferably 10% by weight or less. If there is too much propylene·α-olefin random copolymer, there is a risk that the rigidity, heat resistance, etc. of the film will decrease.
[0059] The propylene·α-olefin random copolymer blended in the base material layer is a random copolymer of propylene and an appropriate α-olefin excluding propylene. Examples of the α-olefin include ethylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, etc. These copolymers may be used alone or in combination of two or more. Among the propylene·α-olefin random copolymers, propylene·ethylene random copolymer, propylene·ethylene·1-butene random copolymer, and propylene·1-butene random copolymer are preferred, and propylene·ethylene·1-butene random copolymer is more preferred.
[0060] The surface layer is a resin layer laminated on one or both sides of the base layer. The surface layer is a layer on which secondary processing of the film such as deposition, printing, lamination, etc. is performed. From the viewpoint of recyclability, it is preferable that the resin material constituting the surface layer is mainly made of polypropylene resin, which is the same resin material as the base layer. The polypropylene resin may be the same type of polypropylene resin as the base layer, or a different type of polypropylene resin. For example, when the surface layer is laminated on one side of the base layer, the film can have a one-type two-layer structure or a two-type two-layer structure. In addition, when the surface layer is laminated on both sides of the base layer, the film can have a one-type three-layer structure, a two-type three-layer structure, or a three-type three-layer structure. Furthermore, as a biaxially stretched film having three or more layers, any layer such as an intermediate layer may be laminated between the base layer and the surface layer as necessary.
[0061] In the surface layer, the pentad fraction of the polypropylene resin used is preferably 90% or more from the viewpoint of ensuring the rigidity, heat resistance, dimensional stability, etc. of the film. In addition, when effectively bleeding out antistatic properties or imparting heat sealability, it is also possible to use a low crystalline resin within a range that does not impair the desired physical properties of the laminated film. Examples of low crystalline resins include random copolymers of propylene and α-olefins (excluding propylene), such as propylene-ethylene random copolymers, propylene-ethylene-1-butene random copolymers, and propylene-1-butene random copolymers.
[0062] In the biaxially stretched polypropylene film, additives are appropriately added as necessary. Examples of additives include antioxidants, ultraviolet absorbers, antistatic agents, lubricants, nucleating agents, adhesives, antifogging agents, flame retardants, antiblocking agents, inorganic or organic fillers, etc. Examples of antistatic agents include aliphatic amine compounds such as lauryl diethanolamine, myristyl diethanolamine, and oleyl diethanolamine, aliphatic amide compounds such as lauryl diethanolamide, myristyl diethanolamide, and oleyl diethanolamide, and polyhydric alcohols. The antistatic agent can be added by a known method. For example, a high-concentration master batch may be prepared separately and mixed in any step, or may be mixed in advance with polyolefin powder or polyolefin pellets. When preparing a high-concentration master batch, for example, it can be obtained by heating and kneading a polyolefin resin and an antistatic agent using a known mixer or extruder such as a Banbury mixer, a Henschel mixer, a tumbler mixer, a single-screw extruder, and a multi-screw extruder.
[0063] The thickness of the biaxially stretched polypropylene film is appropriately set depending on the application, etc. For example, it is preferably 9 to 100 μm, more preferably 10 to 80 μm, further preferably 12 to 60 μm, and particularly preferably 12 to 50 μm. In addition, in the biaxially stretched polypropylene film, the thickness of the surface layer is appropriately adjusted within a range that does not impair the desired physical properties of the film. For example, it is preferably 0.1 to 10 μm, more preferably 0.5 to 8 μm.
[0064] As described above, the biaxially oriented polypropylene film of the present invention is a laminated film in which the recycled material (B) is blended in the base layer to reduce the environmental load. In particular, the blended recycled material is characterized in that the blended recycled material satisfies all of the following conditions: melt flow rate (MFR) of 3.0 to 11.0 g / 10 min, melting peak temperature of 145 to 170° C., and melting enthalpy (ΔH) of 87.0 J / g or more, and the blending ratio is 5 to 25% by weight. Conventionally, when recycled raw materials are used as a constituent material of a film, the film performance such as rigidity and heat resistance may be reduced due to the influence of different materials in the recycled raw materials. However, by blending an appropriate amount of recycled raw materials that satisfy all of the above conditions in the base layer, it has become possible to obtain excellent film formability without impairing film performance such as rigidity and heat resistance, regardless of the presence or absence of different materials in the recycled raw materials. Therefore, in the field of resin films in which it has been difficult to use recycled raw materials, it is possible to promote the reuse of recycled raw materials, which can greatly contribute to reducing the environmental load.
[0065] In the biaxially oriented polypropylene film of the present invention, a sealant film can be laminated on the surface layer or the base layer on the side not provided with the surface layer to form a laminate. As the sealant film, a single-layer or multi-layer resin film having heat sealability is preferably used.
[0066] For the sealant film, any suitable resin material having heat sealing properties can be used, but from the viewpoint of recyclability, it is preferable to use polypropylene resin as the main component, which is the same resin material as the base layer and the surface layer. The polypropylene resin can be selected from general polypropylene-based resins. For example, it is selected from at least one of propylene homopolymer, propylene-α-olefin random copolymer such as propylene-ethylene random copolymer and propylene-ethylene-butene random copolymer, or propylene-ethylene block copolymer.
[0067] The sealant film is preferably a non-stretched polypropylene film using the above polypropylene resin. Since the orientation of the film is reduced in the non-stretched film, the heat seal strength is high, and the film is suitable for the sealant film. Note that the term "non-stretched" means a state in which no intentional stretching is applied, and includes the case where unavoidable stretching is applied during film formation, etc.
[0068] The laminate obtained in this manner comprises a biaxially oriented polypropylene film containing recycled raw materials and a sealant layer, and therefore can be suitably used as a film product such as a packaging film that aims to reduce the environmental impact. EXAMPLES
[0069] [Preparation of biaxially oriented polypropylene film] In producing the biaxially stretched polypropylene films of Prototype Examples 1 to 24, the materials described below were mixed and melted based on a predetermined blending ratio (weight %), and co-extruded by a T-die method to obtain a three-layer structure consisting of a base layer and a first surface layer and a second surface layer laminated on both sides of the base layer, to obtain a raw sheet-like material. Next, the raw sheet-like material was stretched 5.0 times in the machine direction (MD) and then 8.0 times in the transverse direction (TD) to obtain a biaxially stretched polypropylene film consisting of the first surface layer, the base layer, and the second surface layer. The blending ratios of the resin materials used in each layer of Prototype Examples 1 to 24 are shown in Tables 1 to 4 described below.
[0070] [Materials used] The following resins were used as the resin material for each layer. For each material, the melt flow rate (MFR) was measured at a test temperature of 230°C using a melt indexer (G-01, manufactured by Toyo Seiki Seisakusho Co., Ltd.) in accordance with JIS K 7210 (2014). The crystallization temperature (°C), melting peak temperature (°C), and melting enthalpy (J / g) of the recycled raw material were measured using a differential scanning calorimeter (DSC214 Polymer, manufactured by NETZSCH). In this measurement, the temperature was raised from 20°C to 200°C at a rate of 10°C / min under a nitrogen gas flow, held at 200°C for 3 minutes, and then the temperature was lowered from 200°C to 20°C at a rate of 10°C / min (1st Run), held at 20°C for 3 minutes, and then the temperature was raised from 20°C to 200°C at a rate of 10°C / min (2nd Run). The exothermic peak temperature from the DSC curve of the first run was taken as the crystallization temperature (°C), and the melting peak temperature and melting enthalpy were determined from the DSC curve of the second run. When multiple melting peaks existed, the highest melting peak temperature was used, and the melting enthalpy was determined by setting a baseline that connected the DSC curve from 50°C to 180°C with a straight line.
[0071] Further, the molecular weight and molecular weight distribution of each material were measured using a high-temperature GPC device (manufactured by Tosoh Corporation, "HLC-8321GPC-HT") under the following conditions. Column: TSKgel GMHHR-H(20)HT x 3 (7.8mm ID x 300mm x 3) Eluent: 1,2,4-trichlorobenzene (0.05% BHT added) Flow rate: 1.0mL / min Detector: RI detector (polarity: -) Column temperature: 140℃ Injection volume: 300μL Molecular weight standards: Standard polystyrene
[0072] <Polypropylene resin (A)> Resin A1: Propylene homopolymer (mesopentad fraction (mmmm) 96.1%, MFR 3.5g / 10min, melting peak temperature 166℃) Resin A2: Propylene homopolymer (mesopentad fraction (mmmm) 95.8%, MFR 4.6g / 10min, melting peak temperature 166℃) Resin A3: Propylene homopolymer (mesopentad fraction (mmmm) 91.0%, MFR 3.0g / 10min, melting peak temperature 163℃)
[0073] <Recycled materials (B)> Resin B1: Biaxially oriented polypropylene film (commercially available, resin composition: 99.4% by weight polypropylene resin, 0.6% by weight polyethylene resin) recycled material (MFR 5.4g / 10min, melting peak temperature 162°C, melting enthalpy 100.2J / g, crystallization temperature 112°C, Mw / Mn: 4.3, Mz+1 / Mw 5.0) Resin B2: Biaxially oriented polypropylene film (commercially available, resin composition: 97.0% by weight of polypropylene resin, 3.0% by weight of polyethylene resin) made from recycled material (MFR 5.7 g / 10 min, melting peak temperature 161°C, melting enthalpy 100.5 J / g, crystallization temperature 114°C, Mw / Mn 4.3, Mz+1 / Mw 4.8) Resin B3: Recycled material consisting of unstretched polypropylene film (commercially available, resin composition: 98.5% by weight polypropylene resin, 1.5% by weight polyethylene resin) (MFR 10.1 g / 10 min, melting peak temperature 150°C, melting enthalpy 87.6 J / g, crystallization temperature 117°C, Mw / Mn 4.6, Mz+1 / Mw 4.9) Resin B4: Recycled material consisting of polypropylene bottles (commercially available, resin composition: mainly polypropylene resin (details unknown)) (MFR 10.1g / 10min, melting peak temperature 140℃, melting enthalpy 86.8J / g, crystallization temperature 102℃, Mw / Mn 4.8, Mz+1 / Mw 4.6)
[0074] <Propylene-α-olefin random copolymer (C)> Resin C1: Propylene-α-olefin random copolymer (MFR 6.0g / 10min, melting peak temperature 162℃)
[0075] <Additives> As an additive, a master batch of an antistatic agent (Resin D1: MFR 7.8 g / 10 min) was used. The concentration of the antistatic agent was adjusted to 9% based on Resin A3.
[0076] [Prototype 1] Prototype example 1 is a film obtained by blending 100% by weight of Resin A3, which is a polypropylene resin, as a first surface layer, 80% by weight of Resin A1, which is a polypropylene resin, 10% by weight of Resin B1, which is a recycled raw material, and 10% by weight of Resin D1, which is an additive (master batch of antistatic agent), as a base layer, and 100% by weight of Resin A3, which is a polypropylene resin, as a second surface layer, and forming it into a film with a thickness of 20 μm.
[0077] [Prototype 2] Prototype 2 is a film obtained by film formation in the same manner as Prototype 1, except that the base layer contained 75% by weight of Resin A1 and 15% by weight of Resin B1.
[0078] [Prototype 3] Prototype 3 is a film obtained by film formation in the same manner as Prototype 1, except that the base layer contained 70% by weight of Resin A1 and 20% by weight of Resin B1.
[0079] [Prototype 4] Prototype 4 is a film obtained by forming the film in the same manner as Prototype 1, except that the base layer contained 65% by weight of resin A1 and 25% by weight of resin B1.
[0080] [Prototype 5] Prototype Example 5 is a film obtained by film production in the same manner as Prototype Example 1, except that the recycled raw material of the base layer of Prototype Example 1 was changed from resin B1 to resin B2, and the base layer contained 85% by weight of resin A1 and 5% by weight of resin B2.
[0081] [Prototype 6] Prototype 6 is a film obtained by forming the same film as in Prototype 1, except that the recycled raw material for the base layer was changed from Resin B1 to Resin B2.
[0082] [Prototype 7] Prototype 7 is a film obtained by forming the same film as in Prototype 2, except that the recycled raw material for the base layer was changed from Resin B1 to Resin B2.
[0083] [Prototype 8] Prototype 8 is a film obtained by forming the same film as in Prototype 3, except that the recycled raw material for the base layer was changed from Resin B1 to Resin B2.
[0084] [Prototype 9] Prototype Example 9 is a film obtained by forming the same film as Prototype Example 4 except that the recycled raw material for the base layer was changed from Resin B1 to Resin B2.
[0085] [Prototype 10] Prototype 10 is a film obtained by film formation in the same manner as Prototype 1, except that the polypropylene resin in the base layer of Prototype 1 was changed from Resin A1 to Resin A2, and the base layer was blended with 2 wt% Resin C1, a propylene-α-olefin random copolymer, and 78 wt% Resin A2.
[0086] [Prototype example 11] Sample 11 was a film obtained by producing the film in the same manner as Sample 10, except that the thickness of the film was 18 μm.
[0087] [Prototype 12] Sample 12 is a film obtained by forming the film in the same manner as Sample 10, except that the base layer contained 68% by weight of Resin A2 and 20% by weight of Resin B1, and the film thickness was 16 μm.
[0088] [Prototype 13] Prototype Example 13 is a film obtained by blending 15% by weight of Resin A3, a polypropylene resin, with the base layer of Prototype Example 10, making Resin A2 58% by weight, and Resin B1 15% by weight, with the rest being the same.
[0089] [Prototype 14] Prototype Example 14 is a film obtained by film formation in the same manner as Prototype Example 10, except that the polypropylene resin in the base layer of Prototype Example 10 was changed from Resin A2 to Resin A1, and the recycled raw material was changed from Resin B1 to Resin B3, and the base layer contained 83% by weight of Resin A1 and 5% by weight of Resin B3.
[0090] [Prototype 15] Sample 15 is a film obtained by forming the film in the same manner as Sample 14, except that the base layer contained 78% by weight of Resin A1 and 10% by weight of Resin B3.
[0091] [Prototype 16] Sample 16 is a film obtained by forming the film in the same manner as Sample 14, except that the base layer contained 68% by weight of Resin A1 and 20% by weight of Resin B3.
[0092] [Prototype 17] Prototype Example 17 is a film obtained by forming the base layer using a mixture of 87 wt% resin A1, 3 wt% resin C1, and 10 wt% resin D1 without using any recycled raw materials, but otherwise using the same process as Prototype Example 1.
[0093] [Prototype 18] Prototype 18 is a film obtained by film formation in the same manner as Prototype 1, except that the base layer contained 87% by weight of Resin A1 and 3% by weight of Resin B1.
[0094] [Prototype Example 19] Prototype 19 is a film obtained by film formation in the same manner as Prototype 5, except that the base layer contained 60% by weight of Resin A1 and 30% by weight of Resin B2.
[0095] [Prototype Example 20] Prototype 20 is a film obtained by forming the same film as in Prototype 2, except that the recycled raw material for the base layer was changed from Resin B1 to Resin B4.
[0096] [Prototype Example 21] Prototype 21 is a film obtained by forming the same film as in Prototype 3, except that the recycled raw material for the base layer was changed from Resin B1 to Resin B4.
[0097] [Prototype Example 22] Prototype 22 is a film obtained by forming the base layer in the same manner as Prototype 1, except that no recycled materials were used and 90% by weight of Resin A3 was used.
[0098] [Prototype Example 23] Prototype 23 is a film obtained by forming the same film as in Prototype 1, except that the propylene resin in the base layer was changed from Resin A1 to Resin A3.
[0099] [Prototype Example 24] Sample 24 is a film obtained by forming the film in the same manner as Sample 14, except that the base layer contained 58% by weight of Resin A1 and 30% by weight of Resin B3.
[0100] [Table 1]
[0101] [Table 2]
[0102] [Table 3]
[0103] [Table 4]
[0104] The performance of the biaxially oriented polypropylene films of Examples 1 to 24 was evaluated for haze, heat shrinkage, tensile modulus, dimensional stability, and film formability. The results and evaluations of each test are shown in Tables 5 to 8 below, together with the physical properties of the recycled raw materials in each example.
[0105] [Haze] Haze (%) is an index of transparency, and was measured using a haze meter (NDH-8000, manufactured by Nippon Denshoku Industries Co., Ltd.) according to a test method conforming to JIS K 7136 (2000). For the biaxially oriented polypropylene films of prototypes 1 to 24, a haze value of 5.0% or less was determined to be good, which is the transparency required for a packaging film.
[0106] [Heat shrinkage rate] The heat shrinkage rate (%) was measured based on the heat shrinkage rate test in accordance with JIS Z 1712 (2009). In this test, test pieces (width 15 mm, length 150 mm) were cut out from the films of each prototype 1 to 24, and marks were made at 100 mm intervals in the center of the sample. The test pieces were then heated at 150°C for 5 minutes, and the lengths between the marks in the machine direction (MD) and the transverse direction (TD) of the test pieces after heating were measured. From the measured machine direction and transverse direction lengths after heating, the rate of change relative to the machine direction and transverse direction lengths before heating was calculated as the heat shrinkage rate (%). A heat shrinkage rate (%) of 10% or less was judged to be good.
[0107] [Tensile modulus] The tensile modulus (GPa) was measured by cutting out 15 mm x 200 mm test pieces from the films obtained in Samples 1 to 24 using a tensile tester (ORIENTEC Co., Ltd., RTF-1310) based on the test method for plastic tensile properties conforming to JIS K 7127 (1999). Next, the tensile modulus of the film in each of the machine direction (MD) and transverse direction (TD) was measured using a tensile tester (ORIENTEC Co., Ltd., RTF-1310) based on the test method for plastic tensile properties conforming to JIS K 7127 (1999) under the conditions of a chuck distance of 100 mm and a tensile speed of 200 mm / min. In the measurement results, the product was judged to be good when the machine direction (MD) modulus was 2.0 GPa or more and the transverse direction (TD) modulus was 4.0 GPa or more.
[0108] [Dimensional stability] Using a thermomechanical measuring device (TA Instruments Japan, Q400), the dimensional change rates (%) in the machine direction (MD) at 120°C and 140°C were calculated according to the procedure described below, and the dimensional change rate (L 140 ) and dimensional change rate at 120°C (L 120 ) and the difference (L 140 -L 120 ) was calculated as the dimensional stability. Products with a dimensional stability of 15 or less were judged to be non-defective.
[0109] In measuring the dimensional change rate, test pieces (width 4 mm, length 25 mm) were cut from the films of prototypes 1 to 24 in the machine direction (MD). The machine direction (MD) of the test piece was set as the tensile direction, and the chuck distance was set to about 8 mm in the sample holder, and the test piece was fixed to the probe of the thermomechanical device. The length (L0) of the test piece before heating was read by applying a load of 0.32 N to the test piece. The test piece was heated from 30°C to 150°C at a heating rate of 20°C / min while applying a load of 0.32 N in the machine direction, and the length (L1) of the test piece in the machine direction (MD) when it reached 120°C and the length (L2) of the test piece in the machine direction (MD) when it reached 140°C were read, respectively. The lengths (L0), (L1), and (L2) of the test piece before and after heating were substituted into the following formulas (iii) and (iv), and the dimensional change rate at 120°C (L 120 ) and dimensional change rate at 140°C (L 140 ) was calculated. L 120 (%)={(L1-L0) / L0}×100 … (iii) L 140 (%)={(L2-L0) / L0}×100 … (iv)
[0110] [Film forming property] In judging the film-forming properties, appearance defects such as uneven stretching were visually checked during the film-forming of the films of prototypes 1 to 24, and a good appearance was judged as "○", and a poor appearance was judged as "×".
[0111] [Table 5]
[0112] [Table 6]
[0113] [Table 7]
[0114] [Table 8]
[0115] [Results and Discussion] Prototype 17 is a biaxially oriented polypropylene film with a resin composition that does not contain recycled materials and is mainly composed of a highly crystalline polypropylene resin (resin A1). As shown in Table 7, Prototype 17 has good film performance in terms of haze, heat shrinkage rate, tensile modulus, dimensional stability, and film formability. It is preferable that other films containing recycled materials have film performance similar to that of the film of Prototype 17.
[0116] Prototype Examples 1-4 and 18 are examples in which a highly crystalline polypropylene resin (resin A1) is used as the main raw material of the base layer, and resin B1 is used as the recycled raw material, with the amount of each being adjusted. Similarly, Prototype Examples 5-9 and 19 are examples in which resin B2 is used as the recycled raw material, with the amount of each being adjusted. Prototype Examples 14-16 and 24 are examples in which resin B3 is used as the recycled raw material, with the amount of each being adjusted. Prototype Examples 20 and 21 are examples in which resin B4 is used as the recycled raw material, with the amount of each being adjusted.
[0117] Among the films of the above-mentioned prototypes, the films that did not obtain sufficient film performance were prototypes 19 to 21 and 24. Comparing the films of prototypes 19 and 24 with other films that obtained good film performance, the films of prototypes 19 and 24 contained an excessive amount of recycled raw materials compared to the other films. On the other hand, prototypes 20 and 21 were equivalent to films with a good blend ratio of recycled raw materials. From these, it is considered that the physical properties of resin B4 blended in prototypes 20 and 21 are not favorable as a recycled raw material.
[0118] Therefore, from the comparison of the physical properties of the recycled raw materials (resins B1, B2, B3) that gave good results with those of the recycled raw material of resin B4, it is considered that the preferred physical properties of the recycled raw material are an MFR of 11.0 g / 10 min or less, a melting peak temperature of 145°C or higher, a melting enthalpy of 87.0 J / g or higher, and a crystallization temperature of 105°C or higher. Among these physical properties, the lower limit of the MFR is considered to be about 3 g / 10 min in consideration of the fluidity of the resin. The upper limit of the melting peak temperature is considered to be about 170°C in consideration of a practically usable resin molded product. Also, in the recycled raw material, from the comparison between resins B1, B2, B3 and resin B4, it is considered preferable that the molecular weight distribution (Mw / Mn, Mz+1 / Mw) determined by GPC measurement satisfies Mz+1 / Mw ≧ 4.7 along with the relationship Mw / Mn < Mz+1 / Mw.
[0119] Next, the preferred blending ratio of the recycled raw material is examined. In Pilot Example 19 (resin B2) and Pilot Example 24 (resin B3), the blending ratio is considered to have been excessive. Therefore, from Pilot Examples 1 to 4, 18 (resin B1), Pilot Examples 5 to 9 (resin B2), and Pilot Examples 14 to 16 (resin B3) that gave good results, the preferred blending ratio of the recycled raw material is considered to be 25% by weight or less. Considering the perspective of reducing environmental impact, it is preferable that the blending ratio of the recycled raw material contains about 5% by weight. Then, the preferred blending ratio of the recycled raw material that achieves both good film performance and a contribution to the environment is considered to be about 5 to 25% by weight.
[0120] Pilot Example 10 is a film in which the main raw material of the base material layer is changed to another highly crystalline polypropylene resin (resin A2) compared to Pilot Example 1, and a propylene·α-olefin random copolymer (resin C1) is blended. In Pilot Example 10, film performance almost equivalent to that of Pilot Example 1 was obtained. Thus, even when a small amount of propylene·α-olefin random copolymer was blended in the base material layer, no decrease in film performance was observed. The propylene·α-olefin random copolymer can be added in an amount such that the blending amount of the propylene resin is not insufficient, and for example, 10% by weight or less is considered preferable.
[0121] In addition, prototypes 11 to 13 are films in which some changes have been made to the film of prototype 10. Prototype 11 is a film with a reduced thickness. Prototype 12 is a film in which the amount of recycled material (resin B1) has been increased. Prototype 13 is a film in which a small amount of low crystalline polypropylene resin (resin A3) has been added to the base layer. All of prototypes 11 to 13 showed good film performance. From prototype 11, it is considered that there will be no significant change in film performance if the thickness is adjusted within the range of the thickness required for the film. From prototype 12, it was found that even in a film in which a small amount of propylene-α-olefin random copolymer is blended in the base layer, good film performance can be obtained even if the amount of recycled material is increased within the range of 5 to 25% by weight. From prototype 13, it was found that good film performance can be obtained even if a small amount of low crystalline polypropylene resin is included in a base layer mainly made of highly crystalline polypropylene resin.
[0122] In order to study the main raw material polypropylene resin, in prototype 22, a low-crystalline polypropylene resin (resin A3) was used as the main raw material to produce a biaxially oriented polypropylene film that did not contain recycled raw materials. The film of prototype 22 did not have the required rigidity due to insufficient tensile modulus in the transverse (TD) direction, and furthermore, the dimensional stability was insufficient. This is thought to be due to the low crystallinity of the polypropylene resin, which reduced the rigidity and heat resistance of the film.
[0123] Moreover, prototype 23 is a film in which prototype 22 is blended with 10% by weight of resin B1 as a recycled raw material, and corresponds to a film in which the high crystalline polypropylene resin (resin A1) of the base layer of prototype 1 is changed to a low crystalline polypropylene resin (resin A3). In prototype 23, the dimensional stability was insufficient. This is thought to be because the heat resistance and the like were reduced due to the low crystallinity of the polypropylene resin as in prototype 22, and is thought to indicate that the crystallinity of the polypropylene resin, which is the main raw material of the film, affected the film performance regardless of the presence or absence of recycled raw materials.
[0124] Based on the evaluation of each prototype, it was shown that the conditions for not impairing the performance of the longitudinal and transverse elastic modulus, dimensional stability (difference between the longitudinal dimensional change rate at 140℃ and the dimensional change rate at 120℃), and longitudinal and transverse thermal shrinkage rates in films containing recycled materials are that the main raw material of the base layer is 55% or more by weight of highly crystalline polypropylene resin with a mesopentad fraction of 95% or more, and the recycled raw materials satisfy all of the following conditions: MFR 3.0-11.0g / 10min, melting peak temperature 145-170℃, and melting enthalpy 87.0J / g or more, and the blending ratio is 5-25% by weight. It was also shown that even when propylene-α-olefin random copolymer is blended, the film performance is not impaired if it is blended at about 10% by weight or less. [Industrial Applicability]
[0125] In the biaxially oriented polypropylene film of the present invention, by using recycled raw materials that satisfy all of the melt flow rate, melt flow rate peak temperature, and melt enthalpy under the specified conditions, it is possible to obtain excellent film formability without impairing film performance such as rigidity and heat resistance. Therefore, it is possible to provide a biaxially oriented polypropylene film and a laminate using this film that can contribute to reducing the environmental load, and they are promising as replacements for conventional biaxially oriented polypropylene films and their laminates.
Claims
1. A base layer and a surface layer laminated on one side or both sides of the base layer, A laminated film in which recycled materials derived from a molded product mainly made of polypropylene resin are blended in the base layer, The elastic modulus in the machine direction (MD) is 2.0 GPa or more and the elastic modulus in the transverse direction (TD) is 4.0 GPa or more, as measured in accordance with JIS K 7127 (1999); The laminated film has a difference (L140-L120) of 15 or less between the dimensional change rate L140 (%) in the machine direction (MD) at 140°C and the dimensional change rate L120 (%) in the machine direction (MD) at 120°C when the temperature is increased from 30°C to 150°C at a rate of 20°C / min and a load of 0.32 N is applied in the machine direction (MD), as measured by a thermomechanical measuring apparatus (TMA); The substrate layer is 55% by weight or more of a polypropylene resin (A) having a mesopentad fraction (mmmm) of 95% or more; 5 to 25% by weight of the recycled raw material (B) having a melt flow rate (MFR) of 3.0 to 11.0 g / 10 min, a melting peak temperature measured by a differential scanning calorimeter (DSC) in accordance with JIS K 7122 (2012) of 145 to 170° C., and a melting enthalpy (ΔH) of 87.0 J / g or more; The resin mixture is made of at least two different resins including A biaxially oriented polypropylene film.
2. The biaxially oriented polypropylene film according to claim 1, wherein the recycled raw material (B) has a crystallization temperature of 105°C or higher as measured by a differential scanning calorimeter (DSC) in accordance with JIS K 7122 (2012).
3. The biaxially oriented polypropylene film according to claim 1 or 2, wherein the recycled raw material (B) has a molecular weight distribution (Mw / Mn, Mz+1 / Mw) determined by gel permeation chromatography (GPC) measurement that satisfies Mw / Mn<Mz+1 / Mw and Mz+1 / Mw≧4.
7. Mw: Weight average molecular weight Mn: number average molecular weight Mz+1: Z+1 average molecular weight
4. 3. The biaxially oriented polypropylene film according to claim 1, wherein the base layer contains 10% by weight or less of a propylene-α-olefin random copolymer (C).
5. The biaxially oriented polypropylene film according to claim 3, wherein the base layer contains 10% by weight or less of a propylene-α-olefin random copolymer (C).
6. A laminate comprising the biaxially oriented polypropylene film according to claim 1 or 2 and a sealant film laminated thereon.
7. A laminate comprising the biaxially oriented polypropylene film according to claim 3 and a sealant film laminated thereon.
8. A laminate comprising the biaxially oriented polypropylene film according to claim 4 and a sealant film laminated thereon.
9. A laminate comprising the biaxially oriented polypropylene film according to claim 5 and a sealant film laminated thereon.
10. The laminate according to claim 6, wherein the sealant film is a non-oriented polypropylene film.
11. The laminate according to claim 7, wherein the sealant film is a non-oriented polypropylene film.
12. The laminate according to claim 8, wherein the sealant film is a non-oriented polypropylene film.
13. The laminate according to claim 9, wherein the sealant film is a non-oriented polypropylene film.
Citation Information
Patent Citations
Stretched polypropylene film
JP2014055283A
Dual axis extension polypropylene film for producing bag by melting
JP2021133509A
